2019
DOI: 10.3390/electronics8070800
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness Assessment of a Nanocrystalline Sleeve Ferrite Core Compared with Ceramic Cores for Reducing Conducted EMI

Abstract: The interconnection of different electronic devices or systems through cables is becoming more difficult due to the hard restrictions related to electromagnetic compatibility (EMC) in order to comply with requirements. Therefore, the use of EMC components is a good solution to manage the problems associated with the filtering of electromagnetic interference (EMI) in cables and to pass the compliance test. In this sense, sleeve ferrite cores become a very interesting solution since they can be set around a wire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…In these photographs, it is possible to observe the internal structure and the grain size of MnZn (a) and NiZn (b) ceramic materials. The results presented in [19,20] highlighted the great suitability of NC EMI suppressors to filter electromagnetic interference throughout the frequency band from 100 kHz to 100 MHz. Furthermore, data obtained from its magnetic properties indicate that this EMC solution could also provide good performance in terms of EMI suppression at higher frequencies.…”
Section: Nanocrystalline Core Descriptionmentioning
confidence: 91%
See 2 more Smart Citations
“…In these photographs, it is possible to observe the internal structure and the grain size of MnZn (a) and NiZn (b) ceramic materials. The results presented in [19,20] highlighted the great suitability of NC EMI suppressors to filter electromagnetic interference throughout the frequency band from 100 kHz to 100 MHz. Furthermore, data obtained from its magnetic properties indicate that this EMC solution could also provide good performance in terms of EMI suppression at higher frequencies.…”
Section: Nanocrystalline Core Descriptionmentioning
confidence: 91%
“…Nanocrystalline sleeve core represents an innovative and increasingly used solution for EMI suppression in cables. This solution has demonstrated excellent suitability to reduce interferences from the low-frequency region to the mid-frequency range [19,20]. In this sense, some researchers have investigated the use of NC structure compositions to make EMC components because this kind of core can reduce its volume by 50-80% and yield greater magnetic properties and insertion losses than conventional ceramic components [21][22][23][24].…”
Section: Applications Of Emi Suppressor Sleeve Coresmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main advantages of MnZn and NiZn materials is the possibility of creating cores with many different shapes and the possibility of halving them without modifying their internal structure [17,18]. Preliminary studies have shown that NC sleeve ferrite cores provide a significant effectiveness when used as an EMI suppressor [17,19,20]. Nevertheless, the internal structure and manufacturing process have traditionally made it complicated to obtain a split-core sample that can be used as a snap ferrite, keeping its effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…This analysis is performed through an experimental measurement setup that is compared with the results obtained through a finite element method (FEM) simulation model. The simulation model helps to determine the study's accuracy, specifically in the high-frequency range where parasitic elements may affect the experimental results [20]. Likewise, the stability of three solid (not split) and split cable ferrites based on different compositions are characterized in order to determine the influence of DC currents on the impedance response provided.…”
Section: Introductionmentioning
confidence: 99%